2020
DOI: 10.2196/20328
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Disorders and Associated Risk Factors in Quarantined Adults During the COVID-19 Outbreak in China: Cross-Sectional Study

Abstract: Background People undergoing mass home- and community-based quarantine are vulnerable to mental health disorders during outbreaks of coronavirus disease (COVID-19), but few studies have evaluated the associated psychosocial factors. Objective This study aimed to estimate the prevalence of anxiety and depressive symptoms and identify associated demographic and psychosocial factors in the general Chinese population during the COVID-19 pandemic quarantine … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
157
5
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(189 citation statements)
references
References 29 publications
17
157
5
10
Order By: Relevance
“…They reported 44 prevalence rates (2 from one study ( Papandreou et al, 2020 )), making a total of 161,556 individuals. Regarding study location, China was the most frequent country with 13 studies ( Ahmed et al, 2020a ; Choi et al, 2020 ; Elhai et al, 2020 ; Fu et al, 2020 ; Gao et al, 2020 ; Guo et al, 2020 ; Huang and Zhao, 2020 ; Lei et al, 2020 ; Liu et al, 2020 ; Shi et al, 2020 ; C. Wang et al, 2020a ; Y. Wang et al, 2020 ; Zhao et al, 2020 ), followed by 12 European studies ( Bäuerle et al, 2020 ; Forte et al, 2020 ; Fullana et al, 2020 ; Hyland et al, 2020 ; Ozamiz-Etxebarria et al, 2020 ; Papandreou et al, 2020 ; Paulino et al, 2020 ; Pieh et al, 2020 ; Rettie and Daniels, 2020 ; Rodríguez-Rey et al, 2020 ; Shevlin et al, 2020 ; Solomou and Constantinidou, 2020 ), 7 Middle Eastern studies ( Alkhamees et al, 2020 ; Arafa et al, 2020 ; Ayhan Başer et al, 2020 ; Horesh et al, 2020 ; Moghanibashi-Mansourieh, 2020 ; Özdin and Bayrak Özdin, 2020 ; Palgi et al, 2020 ), 4 Central and South American studies( Cortés-Álvarez et al, 2020 ; Fernández et al, 2020 ; Galindo-Vázquez et al, 2020 ; Huarcaya-Victoria et al, 2020 ; Orellana and Orellana, 2020 ), 5 South Asian studies ( Al Banna et al, 2020 ; Islam et al, 2020 ; Kazmi et al, 2020 ; Verma and Mishra, 2020 ) and 2 Australian studies ( Newby et al, 2020 ; Stanton et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported 44 prevalence rates (2 from one study ( Papandreou et al, 2020 )), making a total of 161,556 individuals. Regarding study location, China was the most frequent country with 13 studies ( Ahmed et al, 2020a ; Choi et al, 2020 ; Elhai et al, 2020 ; Fu et al, 2020 ; Gao et al, 2020 ; Guo et al, 2020 ; Huang and Zhao, 2020 ; Lei et al, 2020 ; Liu et al, 2020 ; Shi et al, 2020 ; C. Wang et al, 2020a ; Y. Wang et al, 2020 ; Zhao et al, 2020 ), followed by 12 European studies ( Bäuerle et al, 2020 ; Forte et al, 2020 ; Fullana et al, 2020 ; Hyland et al, 2020 ; Ozamiz-Etxebarria et al, 2020 ; Papandreou et al, 2020 ; Paulino et al, 2020 ; Pieh et al, 2020 ; Rettie and Daniels, 2020 ; Rodríguez-Rey et al, 2020 ; Shevlin et al, 2020 ; Solomou and Constantinidou, 2020 ), 7 Middle Eastern studies ( Alkhamees et al, 2020 ; Arafa et al, 2020 ; Ayhan Başer et al, 2020 ; Horesh et al, 2020 ; Moghanibashi-Mansourieh, 2020 ; Özdin and Bayrak Özdin, 2020 ; Palgi et al, 2020 ), 4 Central and South American studies( Cortés-Álvarez et al, 2020 ; Fernández et al, 2020 ; Galindo-Vázquez et al, 2020 ; Huarcaya-Victoria et al, 2020 ; Orellana and Orellana, 2020 ), 5 South Asian studies ( Al Banna et al, 2020 ; Islam et al, 2020 ; Kazmi et al, 2020 ; Verma and Mishra, 2020 ) and 2 Australian studies ( Newby et al, 2020 ; Stanton et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…All studies measured anxiety using symptom-based scales: 17 used the Generalized Anxiety Disorder scale (GAD) ( Bäuerle et al, 2020 ; Choi et al, 2020 ; Fu et al, 2020 ; Fullana et al, 2020 ; Galindo-Vázquez et al, 2020 ; Gao et al, 2020 ; Huang and Zhao, 2020 ; Huarcaya-Victoria et al, 2020 ; Hyland et al, 2020 ; Islam et al, 2020 ; Palgi et al, 2020 ; Papandreou et al, 2020 ; Pieh et al, 2020 ; Rettie and Daniels, 2020 ; Shevlin et al, 2020 ; Shi et al, 2020 ; Solomou and Constantinidou, 2020 ), 15 used the Depression, Anxiety and Stress Scale (DASS) ( Alkhamees et al, 2020 ; Arafa et al, 2020 ; Al Banna et al, 2020 ; Cortés-Álvarez et al, 2020 ; Elhai et al, 2020 ; Kazmi et al, 2020 ; Moghanibashi-Mansourieh, 2020 ; Newby et al, 2020 ; Orellana and Orellana, 2020 ; Ozamiz-Etxebarria et al, 2020 ; Paulino et al, 2020 ; Rodríguez-Rey et al, 2020 ; Stanton et al, 2020 ; Verma and Mishra, 2020 ; C. Wang et al, 2020a ), 2 used the Zung Self-rating Anxiety Scale (SAS) ( Lei et al, 2020 ; Y. Wang et al, 2020 ), 2 used State-Trait Anxiety Inventory (STAI) ( Forte et al, 2020 ; Liu et al, 2020 ), 4 used the Beck Anxiety Inventory (BAI) ( Ahmed et al, 2020b ; Ayhan Başer et al, 2020 ; Horesh et al, 2020 ; Zhao et al, 2020 ), 2 used Hospital Anxiety and Depression Scale (HADS) ( Guo et al, 2020 ; Özdin and Bayrak Özdin, 2020 ) and one used Brief Symptom Inventory-53 (BSI-53) ( Fernández et al, 2020 ). The reported cut-off points used to classify anxiety are shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Initial reports have suggested that having a diagnosis of cancer is already a significant risk factor for the development of anxiety and/or depression during the COVID-19 pandemic [8].…”
Section: Introductionmentioning
confidence: 99%
“…The media has reported countless anecdotes of anxiety, depression, [1][2][3][4] and domestic violence, [5][6][7] while scienti c journals have published numerous case reports and clinical studies from all over the world. [8][9][10] As of July 29, 2020, a simple PubMed search of "covid 19…”
Section: Introductionmentioning
confidence: 99%